2023
DOI: 10.3847/1538-4357/acc9c3
|View full text |Cite
|
Sign up to set email alerts
|

A Diverse Population of z ∼ 2 ULIRGs Revealed by JWST Imaging

Abstract: Four ultraluminous infrared galaxies (ULIRGs) observed with JWST/NIRcam in the Cosmos Evolution Early Release Science program offer an unbiased preview of the z ∼ 2 ULIRG population. The objects were originally selected at 24 μm and have strong polycyclic aromatic hydrocarbon emission features observed with Spitzer/Infrared Spectrometer. The four objects have similar stellar masses of ∼1011 M ⊙ but otherwise are quite diverse. One is an isolated disk galaxy, but it has an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The SMG + quasar scenario could also explain the observed velocity offsets up to several hundred kilometers per second. The merging of two gas-rich galaxies can trigger starburst and explain the observed HyLIRG-level luminosities, as has been demonstrated in the cases of ULIRGs (e.g., Riechers 2011; Ivison et al 2019;Huang et al 2023). In fact, DW003a has extended CO morphology, implying a second gas clump or galaxy at almost identical redshifts at a distance of ∼90 kpc from the main component.…”
Section: Origin Of the Observed Positional And Velocity Offsetsmentioning
confidence: 63%
“…The SMG + quasar scenario could also explain the observed velocity offsets up to several hundred kilometers per second. The merging of two gas-rich galaxies can trigger starburst and explain the observed HyLIRG-level luminosities, as has been demonstrated in the cases of ULIRGs (e.g., Riechers 2011; Ivison et al 2019;Huang et al 2023). In fact, DW003a has extended CO morphology, implying a second gas clump or galaxy at almost identical redshifts at a distance of ∼90 kpc from the main component.…”
Section: Origin Of the Observed Positional And Velocity Offsetsmentioning
confidence: 63%
“…It has been proposed that when a host experiences bulge growth, e.g., through merging, a central black hole will accrete rapidly (Hopkins et al 2006). Additionally, infrared observations have shown that AGNs are typically present in galaxies with intense star formation (Farrah et al 2003;Rosario et al 2012;Santini et al 2012;Cresci et al 2015;Dai et al 2018;Shin et al 2019;Xie et al 2021;Huang et al 2023). However, it is also believed that AGNs play a role in suppressing star formation (Croton et al 2006;Ciotti et al 2010;Fabian 2012;Page et al 2012;Jin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While in Kartaltepe et al (2012), the majority of ULIRGs display merger-like morphologies with distorted and irregular features. Recent James Webb Space Telescope (JWST) observations have also revealed that previously considered isolated ULIRGs are, in fact, merging systems, with a heavily obscured second nucleus buried in the galaxy center (Huang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that confirms the increased star formation activity in merger systems (e.g., Larson & Tinsley 1978;Barton et al 2000;Lin et al 2007;Shah et al 2022), while mergers can also result in the formation of a bulge (Aguerri et al 2001). Studies have shown that nearly all nearby ULIRGs are interacting merger systems, revealing a substantial correlation between mergers and star formation activities (e.g., Sanders et al 1988;Sanders & Mirabel 1996;Huang et al 2023). However, in the high redshift universe, things became complicated.…”
Section: Introductionmentioning
confidence: 99%